Nation‐building in contemporary Germany: the strange conversion of Hitler's 'word made of stone'. Issue 4 (30th August 2013) - Beckstein, Martin
Abstract: This article examines the contending redefinitions of national identity in contemporary Germany's memorial culture, focusing particularly on the ensemble of monuments and parade fields known as the former Nazi Party rally grounds in Nuremberg. In a detailed case study, I analyse the recent conversion of one of the physical remnants of National Socialism – Albert Speer's transformer station – into a fast‐food restaurant and interpret this conversion as a novel contribution to the discourse on German nationhood. I argue that the provocative commercial reutilisation of the former Nazi monument gives expression to a renewed self‐confidence that Germany has gained from displaying a willingness to face up to its past as perpetrator nation. While the intervention thus deviates from the self‐indicting spirit that had been characteristic for Germany's memorial culture after World War II, an ironic note is conspicuous in this act of commemorative politics that indicates a way of dealing with the fascist legacy that is, surprisingly in some respects, superior to more conventional memory strategies.